The EFFECT OF THE USING EXPOSITORY METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT TO TENTH GRADE STUDENTS OF SMA NEGERI 1 ANGKOLA TIMUR - Alfred - Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: This study aims to know whether there is a significant effect of the expository method on the students’ achievement in writing recount text to the tenth grades student of SMA Negeri 1 Angkola Timur. The research was conducted by using experimental method (pretest posttest one group design) with 33 students as the sample and they were taken by using cluster sampling technique from 102 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of the using expository method was 2.85 (good category) and b) the average of students’ achievement in writing recount text before using expository method was 68.18 (enough category) and after using picture and picture model was 77.06 (good category). Furthermore, based on inferential statistic by using ttest one tail, it could be found ttable was less than ttest (7.545 > 1.695). It means, there is a significant effect of the using expository method on the students’ achievement in writing recount text to the tenth grades student of SMA Negeri 1 Angkola Timur. Keywords: expository method and writing recount text